Penerapan Disiplin Melalui Budaya Sekolah pada Siswa Kelas IX MTs Ponpes Islam Al Iman Muntilan - Munaya Ulil Ilmi (Instructional Development Journal, 2020)
This study aims to describe the Discipline Implementation Through the Culture of School to the Students of IX Class of MTs Ponpes Islam Al Iman Muntilan. This research is a descriptive qualitative research. The results showed that the Discipline Implementation Through the Culture of School to the Students of IX Class of MTs Ponpes Islam Al Iman Muntilan was implemented by establishing school rules, inside and outside the classroom, accustoming positive things such as memorizing the Al-Quran before starting learning, giving punishment to students who violate rules, as well as giving awards such as praise, sashes, and even certificates to students who adopt a culture of discipline with full awareness. Principals, teachers, and other authorities assertively handle undisciplined students.Penelitian ini bertujuan untuk mendeskripsikan penerapan disiplin melalui budaya sekolah pada siswa kelas IX MTs Ponpes Islam Al Iman Muntilan. Penelitian ini ialah penelitian kualitatif jenis deskriptif. Hasil penelitian menunjukkan bahwa penerapab disiplin melalui budaya sekolah pada siswa kelas IX MTs Ponpes Islam Al Iman muntilan dilaksanakan dengan cara menetapkan peraturan sekolah, di dalam, dan diluar kelas, membiasakan hal positif seperti menghafal Al Quran sebelum memulai pembelajaran, memberikan hukuman kepada siswa yang melanggar peraturan, serta memberikan penghargaan seperti pujian, selempang, bahkan serfitikat kepada siswa yang menerapkan budaya disiplin dengan penuh kesadaran. Kepala sekolah, guru, serta pihak yang berwajib lainnya dengan tegas memberikan penanganan kepada siswa yang tidak disiplin.